2002
DOI: 10.1295/polymj.34.841
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Synthesis of Layered Polymer Crystals

Abstract: ABSTRACT:A new solvent-free synthetic process of layered polymer crystals as novel organic intercalation materials from (Z, Z)-muconic acid is described. This process includes the monomer synthesis, topochemical polymerization, transformation to poly(muconic acid), and intercalation. Alkylammonium muconate monomers were prepared by grinding muconic acid and the corresponding alkylamines in a ceramic mortar without any solvent. Topochemical polymerization of the alkylammonium muconates in the crystalline state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…152 This is performed in a simple and convenient procedure by grinding the PMA crystals in the presence of a neat amine in a mortar without any solvent. The intercalation proceeded regardless of the kind of the alkylamine used.…”
Section: Materials Design By Organic Intercalationmentioning
confidence: 99%
“…152 This is performed in a simple and convenient procedure by grinding the PMA crystals in the presence of a neat amine in a mortar without any solvent. The intercalation proceeded regardless of the kind of the alkylamine used.…”
Section: Materials Design By Organic Intercalationmentioning
confidence: 99%
“…The results for the intercalation of various mono‐ and diamino‐functionalized azobenzene derivatives into the host PMA crystals are summarized in Table 2. We first attempted the intercalation of MAB‐0 as a commercially available azobenzene using a dispersed system in methanol and a grinding method in the solid state,41 but MAB‐0 was not incorporated into the PMA due to the low basicity of the guest aniline (p K a = 4.6 for aniline). It was also confirmed that aniline was not intercalated into the PMA.…”
Section: Resultsmentioning
confidence: 99%
“…Some mechanical and structural properties have already been revealed with well-defined and highly or partly crystalline polymers [108][109][110][111].A totally solvent-free system for the synthesis of layered polymer crystals was also reported [112].…”
Section: Supramolecular Control Of Stereochemistry Of Polymersmentioning
confidence: 99%